Risk Factors Associated with Healthcare Utilization for Spine Pain. Issue 8 (6th January 2022) - Higgins, Diana M; Han, Ling; Kerns, Robert D; Driscoll, Mary A; Heapy, Alicia A; Skanderson, Melissa; Lisi, Anthony J; Mattocks, Kristin M; Brandt, Cynthia; Haskell, Sally G
Abstract: Objective: This study examined potential risk factors associated with healthcare utilization among patients with spine (i.e., neck and back) pain. Methods: A two-stage sampling approach examined spine pain episodes of care among veterans with a yearly outpatient visit for six consecutive years. Descriptive and bivariate statistics, followed by logistic regression analyses, examined baseline characteristics of veterans with new episodes of care who either continued or discontinued spine pain care. A multivariable logistic regression model examined correlates associated with seeking continued spine pain care. Results: Among 331, 908 veterans without spine pain episodes of care during the 2-year baseline observation period, 16.5% (n = 54, 852) had a new episode of care during the following 2-year observation period. Of those 54, 852 veterans, 37, 025 had an outpatient visit data during the final 2-year follow-up period, with 53.7% (n = 19, 865) evidencing continued spine pain care. Those with continued care were more likely to be overweight or obese, non-smokers, Army veterans, have higher education, and had higher rates of diagnoses of all medical and mental health conditions examined at baseline. Among several important findings, women had 13% lower odds of continued care during the final 2-year observation period, OR 0.87 (0.81, 0.95). Conclusions: A number of important demographics and clinical correlates were associated with increased likelihood of seeking new and continued episodes of care for spine pain; however, further examination of risk factors associated with healthcare utilization for spine pain is indicated.